Intraoperative electroacupuncture relieves remifentanil-induced postoperative hyperalgesia via inhibiting spinal glial activation in rats. Issue 1 (August 2017) - Shi, Changxi; Liu, Yue; Zhang, Wei; Lei, Yishan; Lu, Cui'e; Sun, Rao; Sun, Yu'e; Jiang, Ming; Gu, Xiaoping; Ma, Zhengliang
Background: Accumulating studies have suggested that remifentanil, the widely-used opioid analgesic in clinical anesthesia, can activate the pronociceptive systems and enhance postoperative pain. Glial cells are thought to be implicated in remifentanil-induced hyperalgesia. Electroacupuncture is a complementary therapy to relieve various pain conditions with few side effects, and glial cells may be involved in its antinociceptive effect. In this study, we investigated whether intraoperative electroacupuncture could relieve remifentanil-induced postoperative hyperalgesia by inhibiting the activation of spinal glial cells, the production of spinal proinflammatory cytokines, and the activation of spinal mitogen-activated protein kinases. Methods: A rat model of remifentanil-induced postoperative hyperalgesia was used in this study. Electroacupuncture during surgery was conducted at bilateral Zusanli (ST36) acupoints. Behavior tests, including mechanical allodynia and thermal hyperalgesia, were performed at different time points. Astrocytic marker glial fibrillary acidic protein, microglial marker Iba1, proinflammatory cytokines, and phosphorylated mitogen-activated protein kinases in the spinal cord were detected by Western blot and/or immunofluorescence. Results: Mechanical allodynia and thermal hyperalgesia were induced by both surgical incision and remifentanil infusion, and remifentanil infusion significantly exaggerated and prolonged incision-induced pronociceptive effects. Glial fibrillary acidic protein, Iba1, proinflammatory cytokines (interleukin-1β and tumor necrosis factor-α), and phosphorylated mitogen-activated protein kinases (p-p38, p-JNK, and p-ERK1/2) were upregulated after surgical incision, remifentanil infusion, and especially after their combination. Intraoperative electroacupuncture significantly attenuated incision- and/or remifentanil-induced pronociceptive effects, spinal glial activation, proinflammatory cytokine upregulation, and phosphorylated mitogen-activated protein kinase upregulation. Conclusions: Our study suggests that remifentanil-induced postoperative hyperalgesia can be relieved by intraoperative electroacupuncture via inhibiting the activation of spinal glial cells, the upregulation of spinal proinflammatory cytokines, and the activation of spinal mitogen-activated protein kinases.